Krodha Through the Ages: A Systematic Review of Anger Evidence from Ancient Civilizations to Contemporary Society - Prusty, Nikita (International Research Journal of Ayurveda & Yoga, 2025)
Anger (Krodha), a complex emotional response, has been scrutinized across centuries through religious, philosophical, and psychological lenses. This article traces the evolution of anger as conceptualized in ancient civilizations, particularly within Indian philosophical traditions, and maps its transformation through historical, cultural, and scientific paradigms into contemporary understandings. It draws on classical texts such as the Rig Veda, Manyu Sukta, Ramayana, Mahabharata, Taittiriya Upanishad, Brihadaranyaka Upanishad, Bhagavad Gita, and Patanjali Yoga Sutras, while integrating perspectives from Cultural Contexts and Contemporary Society.